Schoolgirls' experience and appraisal of menstrual absorbents in rural Uganda: a cross-sectional evaluation of reusable sanitary pads. Issue 1 (December 2016) - Hennegan, Julie; Dolan, Catherine; Wu, Maryalice; Scott, Linda; Montgomery, Paul
Abstract Background Governments, multinational organisations, and charities have commenced the distribution of sanitary products to address current deficits in girls' menstrual management. The few effectiveness studies conducted have focused on health and education outcomes but have failed to provide quantitative assessment of girls' preferences, experiences of absorbents, and comfort. Objectives of the study were, first, to quantitatively describe girls' experiences with, and ratings of reliability and acceptability of different menstrual absorbents. Second, to compare ratings of freely-provided reusable pads (AFRIpads) to other existing methods of menstrual management. Finally, to assess differences in self-reported freedom of activity during menses according to menstrual absorbent. Methods Cross-sectional, secondary analysis of data from the final survey of a controlled trial of reusable sanitary padand puberty education provision was undertaken. Participants were 205 menstruating schoolgirls from eight schools in rural Uganda. 72 girls who reported using the intervention-provided reusable pads were compared to those using existing improvised methods (predominately new or old cloth). Results Schoolgirls using reusable pads provided significantly higher ratings of perceived absorbent reliability across activities, less difficulties changing absorbents, and less disgust with cleaning absorbents. There were no significant differences in reports of outside garment soiling (OR 1.00 95%CI 0.51–1.99), or odour (0.84 95%CI 0.40–1.74) during the last menstrual period. When girls were asked if menstruation caused them to miss daily activities there were no differences between those using reusable pads and those using other existing methods. However, when asked about activities avoided during menstruation, those using reusable pads participated less in physical sports, working in the field, fetching water, and cooking. Conclusions Reusable pads were rated favourably. This translated into some benefits for self-reported involvement in daily activities, although reports of actual soiling and missing activities due to menstruation did not differ. More research is needed comparing the impact of menstrual absorbents on girls' daily activities, and validating outcome measures for menstrual management research.